1997
DOI: 10.1017/s0890037x00043360
|View full text |Cite
|
Sign up to set email alerts
|

Control of Palmer Amaranth (Amaranthus palmeri) in Peanut (Arachis hypogaea) with Postemergence Herbicides

Abstract: Seven postemergence (POST) herbicides were evaluated alone and in various mixtures for Palmer amaranth control in peanut from 1992 through 1994. AC 263,222 at rates as low as 0.04 kg/ha controlled ≥ 95% Palmer amaranth. Imazethapyr at rates of 0.05 to 0.07 kg/ha controlled ≥ 90% Palmer amaranth in 2 of 3 yr. Acifluorfen alone or in combination with bentazon or 2,4-DB and lactofen alone controlled > 90% Palmer amaranth in 2 of 3 yr. Bentazon or pyridate failed to provide adequate control (≤ 60%), while 2,4-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 20 publications
4
50
0
2
Order By: Relevance
“…Also, the lactofen product label requires that sequential applications be made at least 14 DAIT, possibly because the level of control does not improve when applied at a shorter interval (Anonymous 2015). Although studies have shown lactofen to have higher activity on Palmer amaranth than acifluorfen, bentazon, or 2,4-DB, many of these studies did not investigate the recovery of Palmer amaranth over time (Grichar 1997a(Grichar , 2008Mayo et al 1995). Gaeddert et al (1997) did record Palmer amaranth control over time and found that acifluorfen and lactofen provided the same level of control 7 d after treatment, but by 28 d after treatment lactofen provided 16% more control than acifluorfen.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the lactofen product label requires that sequential applications be made at least 14 DAIT, possibly because the level of control does not improve when applied at a shorter interval (Anonymous 2015). Although studies have shown lactofen to have higher activity on Palmer amaranth than acifluorfen, bentazon, or 2,4-DB, many of these studies did not investigate the recovery of Palmer amaranth over time (Grichar 1997a(Grichar , 2008Mayo et al 1995). Gaeddert et al (1997) did record Palmer amaranth control over time and found that acifluorfen and lactofen provided the same level of control 7 d after treatment, but by 28 d after treatment lactofen provided 16% more control than acifluorfen.…”
Section: Resultsmentioning
confidence: 99%
“…Porém, Grichar (1997) Mattos (2004) constatou que a melhor época de aplicação do imazapic foi em pós-emergência, sendo que a partir da dose de 120 g ha -1 já houve excelente controle das plantas daninhas e menor efeito fitotóxico na cultura, corroborando com os resultados deste trabalho.…”
Section: Resultsunclassified
“…Effects of POST soybean herbicide treatments on glyphosate-resistant Palmer amaranth control 7 and 21 days after treatment (DAT), and biomass reduction at 21 DAT. (Grichar 1994(Grichar , 1997. At 21 DAT, glufosinate, glyphosate plus 2,4-D choline, dicamba, or fomesafen provided 71% to 92% GR Palmer amaranth control.…”
Section: Palmer Amaranth Biotypesmentioning
confidence: 99%